The Genocide Debate Politicians, Academics, and Victims - Beachler, D. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Neither a case study of a particular genocide nor a work of comparative genocide, this book explores the political constraints and imperatives that motivate debates about genocide in the academic world and, to a lesser extent, in the political arena. The book is an analysis of the ways that political interests shape discourse about genocide.